2016
DOI: 10.3126/nje.v6i3.14762
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among doctors of a tertiary care hospital of eastern India

Abstract: Background: Job satisfaction expresses the extent of congruence between an individual’s expectation of the job and the reward that the job provides.Job satisfaction among doctors is an issue that is of utmost importance because offactors like patient relationships and time pressures associated with managed care. The current study was done to determine the level of job satisfaction in doctors posted in a tertiary care hospital of eastern India and to find out the factors associated with it. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
5
21
1
Order By: Relevance
“…The number of moderately satisfied, satisfied, and very satisfied physicians and dentists and sample sizes were pooled, resulting in an overall weighted percentage of 60% (95% CI 53%-67%), representing 14 113 physicians and dentists with substantial heterogeneity (I 2 = 98.21%; P < .001) ( Figure 4A). 46,47,52,53,55,58,59,81,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Palmer-Morales et al, 40,41 2005 He et al, 87 Esquivel-Molina et al, 45 2007 Huri et al, 93 2016 Salem et al, 92 2018 Beltrán et al, 44 2004 Montenegro et al, 42 insufficient number of studies within each group. This concern was supported by a metaregression of dichotomous data, which suggested that job satisfaction levels did not differ significantly across countries with different income levels, but it was significantly higher among dermatologists (regression coefficient, 0.45; 95% CI, 0.13-0.89; P = .045) compared with other specialties (eAppendix 5 in the Supplement).…”
Section: Studies Were Published Between 1982 and 2018 Primarily Inmentioning
confidence: 99%
“…The number of moderately satisfied, satisfied, and very satisfied physicians and dentists and sample sizes were pooled, resulting in an overall weighted percentage of 60% (95% CI 53%-67%), representing 14 113 physicians and dentists with substantial heterogeneity (I 2 = 98.21%; P < .001) ( Figure 4A). 46,47,52,53,55,58,59,81,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Palmer-Morales et al, 40,41 2005 He et al, 87 Esquivel-Molina et al, 45 2007 Huri et al, 93 2016 Salem et al, 92 2018 Beltrán et al, 44 2004 Montenegro et al, 42 insufficient number of studies within each group. This concern was supported by a metaregression of dichotomous data, which suggested that job satisfaction levels did not differ significantly across countries with different income levels, but it was significantly higher among dermatologists (regression coefficient, 0.45; 95% CI, 0.13-0.89; P = .045) compared with other specialties (eAppendix 5 in the Supplement).…”
Section: Studies Were Published Between 1982 and 2018 Primarily Inmentioning
confidence: 99%
“…Next highest distribution was in the age group of 31-40years with 22.2%. Least was in the age group of 41-50 years.According to age wise distribution, upto 66.7% were middle age group (31-50 years) 5 , 15% were in the age group of 20-30 years in a study done by Cesar Carrillo Garcia 5 in Spain.Increasing age was found to be associated with higher levels of satisfaction 6 . A longitudinal study among Norwegian doctors by Nylenna et al showed positive correlation with age (job satisfaction better with growing age) 7 .…”
Section: Discussionmentioning
confidence: 87%
“…In our study we found, irrespective of nature of employment whether permanent or contract the job satisfaction level remained the same, with doctors being least satisfied (score 2.72) and pharmacist being most satisfied (score 3.2).A study done by Poonam Jaiswal et al, mean job satisfaction was highest for nurses(0.68), followed by doctors(0.66) 12 .A study done by Anne Ene and Adah-Ogoh in Nigeria, more than half (53.2%) of the respondents were dissatisfied with their job 13 .A study done by SharmistaBhattacherjee et al showed more than 50% of the participants were satisfied 6 .Study done by Sharma M 14 and Madaan N 9 showed the same result.But a study done by Chaudary S and Bannerjee A 15 showed job satisfaction to be 40%.A study done in European union 16 showed 25% job dis-satisfaction, where as a study done in Karachi showed only 32% were satisfied with their jobs 17 and 43.6% in a study in Sri Lanka 18 . A study done by Jackie Mamitsa and BanyanaRamasodi, showed 53.4% were not satisfied with their current job and 26.2% of the participants were highly dissatisfied 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Comparable results have been documented from Pakistan (2,7); where mainstream health service providers were satisfied with supervisors/colleagues and job description, but low salaries/benefits/rewards, communication matters, working conditions (15,19) and lack of service structure (20) abetted occupational satiety. Scientist labeled workplace as one of the most important factor to affect doctors; more satisfied being males, older, serving in preclinical/para-clinical departments and having infrequent departmental displacements/postings (21). HAM et al found that diversity of work, positive collegial interactions and teaching experience garnish job satisfaction; while low-slung income, extended working hours/duties, time management disputes and lack of recognition attenuate it (22).…”
Section: Discussionmentioning
confidence: 99%